GLP: planning, recording, and archiving - Withers, Phil (Henry Stewart Talks, 2013)
Prescriptive documents, Study plan, Pivotal document, GLP requirements for contents and amendments, Master schedule, Regulatory inspectors' requests, Descriptive documents, Raw data, Before and during data recording, ALCOA, Data management, Carousel loading, Data audit trail, Source of data generated, Retaining data in the archive, Associated documentation, Environmental data, Concentric series, Archive function, Designated manager, Movement of material into the archive, Retrieval of material, History of document, SOP-security, Conditions which minimise deterioration, Archive indexing, Electronic archiving, Data type / Licence for sale and archive duration, Difficulties in archiving, Discarding archived data